2019
DOI: 10.3390/ijms20081912
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Intestinal Inflammatory Diseases: Molecular Mechanisms of Protection

Abstract: Intestinal inflammatory diseases, such as Crohn’s disease, ulcerative colitis, and necrotizing enterocolitis, are becoming increasingly prevalent. While knowledge of the pathogenesis of these related diseases is currently incomplete, each of these conditions is thought to involve a dysfunctional, or overstated, host immunological response to both bacteria and dietary antigens, resulting in unchecked intestinal inflammation and, often, alterations in the intestinal microbiome. This inflammation can result in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 352 publications
(508 reference statements)
3
96
1
6
Order By: Relevance
“…Curcumin, with the advantages of low‐cost, reliable sources and low side effects, is holding considerable attention for UC treatment. Its significant NF‐κB inhibition, expressed by regulating NF‐κB/IκB pathway and down‐regulating expression of pro‐inflammatory cytokines, was thought to be the key mechanism for the anti‐inflammatory …”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, with the advantages of low‐cost, reliable sources and low side effects, is holding considerable attention for UC treatment. Its significant NF‐κB inhibition, expressed by regulating NF‐κB/IκB pathway and down‐regulating expression of pro‐inflammatory cytokines, was thought to be the key mechanism for the anti‐inflammatory …”
Section: Discussionmentioning
confidence: 99%
“…While the sequence of events in NEC etiology remains unclear, the disease is likely initiated by an excessive stimulation of toll-like receptor 4 (TLR4) by Gram-negative bacteria [31] in the ileum of the premature infant. Activation of this receptor [32][33][34][35][36][37][38] leads to extensive inflammation, denoted by apoptosis of enterocytes along the luminal border, impaired replacement of these enterocytes, increased release of proinflammatory cytokines and chemokines, and, in total, breakdown of the intestinal barrier [39][40][41]. This impaired intestinal barrier allows for greater bacterial translocation [42], leading to increased inflammation via direct contact of pathogenic bacterial antigens with the mucosal immune system [43].…”
Section: Pathogenesis Of Necrotizing Enterocolitismentioning
confidence: 99%
“…demonstrated that curcumin prevented liver damage possibly by modulating NF‐κB translocation (Afrin et al, 2017). Therapeutic potential of curcumin in GI diseases was elaborately summarized (Burge, Gunasekaran, Eckert, & Chaaban, 2019; Kwiecien et al, 2019).…”
Section: Introductionmentioning
confidence: 99%